2016
DOI: 10.1002/jcla.22012
|View full text |Cite
|
Sign up to set email alerts
|

Do Serum Creatinine Levels Show Clinically Significant Fluctuations on Serial Determinations on the Siemens Advia 1800 Analyzer?

Abstract: Mild-to-moderate fluctuations in precision occur in successive serum creatinine determinations. The overwhelming majority of these fluctuations should not affect clinical decision making.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 2 publications
1
3
0
Order By: Relevance
“…Occasional CV values were obtained that were significantly higher than the mean such as 14.08 and 12.06 for ALT and AST, respectively (column 4, entries 2 and 3 in Table 1). This observation reflects a phenomenon that occurs frequently in studies on the reproducibility of values [3,4] higher values of CVs often are found for values that have low means. The ALT sample having the CV value of 14.08 had the following six values determined over the study's time course: 6, 7, 9,7,7,8 with a mean of 7.33 and a standard deviation of 1.03.…”
Section: Stabilities Of Individual Samplessupporting
confidence: 53%
See 2 more Smart Citations
“…Occasional CV values were obtained that were significantly higher than the mean such as 14.08 and 12.06 for ALT and AST, respectively (column 4, entries 2 and 3 in Table 1). This observation reflects a phenomenon that occurs frequently in studies on the reproducibility of values [3,4] higher values of CVs often are found for values that have low means. The ALT sample having the CV value of 14.08 had the following six values determined over the study's time course: 6, 7, 9,7,7,8 with a mean of 7.33 and a standard deviation of 1.03.…”
Section: Stabilities Of Individual Samplessupporting
confidence: 53%
“…In several prior studies, we examined the stabilities of a number of serum analytes included electrolytes [1], glucose [2], BUN [3] and creatinine [3,4] These studies were prompted by specific findings such as slow increases in sodium values on the same samples after ion selective electrode replacement [1], effects of storage of samples prior to analysis [5] and random error in borderline values of creatinine [4]. In view of several recent requests for repeat analysis of several serum enzyme levels, we have extended our studies as part of our quality assurance program to include these critical enzymes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Imprecision in repeat determinations of specific samples can result in confusion concerning diagnosis. This applies especially to analyte values that are "borderline," i.e., that lie close to the lower or upper limit values of the reference range 4 . Imprecision in these cases can result in false positive or false negative test results leading to an incorrect diagnosis.…”
Section: Introductionmentioning
confidence: 99%